2007
DOI: 10.1093/nar/gkm686
|View full text |Cite
|
Sign up to set email alerts
|

Anopheles gambiae miRNAs as actors of defence reaction against Plasmodium invasion

Abstract: The path Plasmodium takes across the Anopheles midgut constitutes the major bottleneck during the malaria transmission cycle. In the present study, using a combination of shot-gun cloning and bioinformatic analysis, we have identified 18 miRNAs from Anopheles gambiae including three miRNAs unique to mosquito. Twelve of them are expressed ubiquitously across the body, independently of gender, while the other six exhibited an expression pattern restricted to the digestive system. Strikingly, the expression patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
200
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(206 citation statements)
references
References 41 publications
4
200
1
1
Order By: Relevance
“…[8][9][10][11][12] Silencing of the main RNA-induced silencing complex (RISC) component was shown to promote the susceptibility of Anopheles gambiae to Plasmodium infection. 13 Similarly, dysfunction in Dicer and RNA-dependent RNA polymerase resulted in a loss of the regulation control of specific surface proteins in Giardia lamblia. 14 These observations indicate that regulatory miRNAs, a subclass of small regulatory RNAs, are present from ancient unicellular protozoans to parasitic helminths and parasitic arthropods.…”
mentioning
confidence: 99%
“…[8][9][10][11][12] Silencing of the main RNA-induced silencing complex (RISC) component was shown to promote the susceptibility of Anopheles gambiae to Plasmodium infection. 13 Similarly, dysfunction in Dicer and RNA-dependent RNA polymerase resulted in a loss of the regulation control of specific surface proteins in Giardia lamblia. 14 These observations indicate that regulatory miRNAs, a subclass of small regulatory RNAs, are present from ancient unicellular protozoans to parasitic helminths and parasitic arthropods.…”
mentioning
confidence: 99%
“…Both conserved and mosquito-specific miRNAs have been found in Anopheles stephensi and A. aegypti (22,23). RNAi depletion of either Dcr1 or Ago1 was shown to result in a higher infection level by Plasmodium berghei parasites in the midgut of Anopheles gambiae mosquitoes (24). In Aedes albopictus and Culex quinquefasciatus, miRNAs were cloned and sequenced, and two were found to be up-regulated owing to West Nile virus infection (25).…”
mentioning
confidence: 99%
“…Interestingly, the expression of four specific miRNA, again including the three unique miRNA, was affected by the presence of Plasmodium. Knocking down Dicer1 and Ago1 mRNAs via gene silencing techniques led to increased susceptibility of the mosquitoes to Plasmodium infection [26][27][28], therefore providing evidence for miR-NA-mediated post-transcriptional regulation of the genes involved in defence reactions, as mosquito genes of the silencing pathway would affect parasite development in the midgut.…”
Section: Mirna In Vector-parasite Interactionsmentioning
confidence: 99%
“…Using a combination of shotgun cloning and bioinformatic analysis, Anopheles mosquito miRNA were analysed, specifically their homology with other species and their localisation within the mosquito [26]. 152 clones were found that could be potential miRNA, however only eighteen met all the criteria to be bona fide miRNA.…”
Section: Mirna In Vector-parasite Interactionsmentioning
confidence: 99%